Problems of Academic Writing: Lexical Errors, their Causes and Correction Strategies - O. L. Dobrynina (Moscow Polytechnic University, 2018)
Lexical errors in students' English writing may be caused by lexical interference, multiple meaning and synonymy of Russian and English words. Russian students studying English as a foreign language often have little notion of the English or Russian word connotation and cannot analyze the word meaning; consequently they make a lot of lexical errors in translating their ideas into English. Typical students' errors and mistakes include usage of a direct word meaning instead of a figurative one, transfer of the given word collocation into all possible collocations of this word, errors in selecting the contextual meaning of a multiple meaning word. We use some methods in teaching students to analyze the contextual meaning of the word and to find the English word for adequate translation: explanation of some problematic situations, cross-lingual matching and translation comparison. As a result students gain metacognitive skills to classify the obtained information and to organize it into linked structures, to analyze the contextual word meaning, to overcome vocabulary disparity and word sense disambiguation.